The Influence of the Work Environment on the Work Productivity of Production Department Employees in the Kesu Cheese Business - Harahap, Lokot Muda; Sherlinda, Azzahra; Manurung, Johanes Adrian; Rumahorbo, Jonathan; Nirwani, Sekar; Prasetyo, Yogi Damanik (Economic: Journal Economic and Business, 2024)
This research aims to determine the influence of the work environment on the work productivity of employees in the production department at the Kesu Cheese business. The sample for this research was 30 respondents who were all production employees. The data collection methods used were interviews, documentation and observation. The data analysis techniques used are descriptive statistical analysis, simple linear regression analysis, coefficient of determination analysis, and t test. The research results show that the work environment has a positive effect on employee work productivity. This is based on the results of multiple linear regression analysis which shows a significance value of 0.000 < 0.05.